Is cartilage- perichondrium composite graft tympanoplasty the ideal treatment for revision tympanoplasty - Tyagi, Brajpal Singh; Tyagi, Sushant; Srivastava, Mohit; Tyagi, Amit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: The objective of the study was to evaluate the anatomical and audiological outcomes of cartilage-perichondrium composite graft tympanoplasty by underlay technique in revision tympanoplasties. Methods: A series of 55 patients who underwent revision tympanoplasty with cartilage-perichondrium composite Island graft, at the department of Otorhinolaryngology, Harsh ENT Hospital, Ghaziabad. Tympanoplasty with cartilage-perichondrium composite island graft was done using underlay technique after slicing the cartilage with help of slicer. Ossiculoplasty was performed as and when needed. Results: Graft uptake rate was found to be 96.36% (53 of the 55 cases) in our study without any serious complications. Audiological outcomes with closure of 94.55% air bone gap within 0 to 30 dB was achieved (p <0.05). Conclusions: Nearly 97% success rate can be achieved with cartilage-perichondrium composite graft tympanoplasty for Revision tympanoplasty.